Bios and ethics in our complex adaptable systems : responsibilities towards our children and our globe - Sass, Hans-Martin (Array, 2019)
We, our bodies and spirits and our natural and social biotopes are complex adaptable systems [CAS’s], interdependent and vulnerable within natural, cultural and political biotopes, longing for life, health and happiness. Clinical and pediatric expertise and ethics are also integrated in many fields of competence and care for our integrated bios and for sustainable biotopes in nature and society. A Bioethical Imperative calls for protecting the complex and interdependent bios in nature and agriculture and in our human social, economic, corporate, cultural, and political bodies for the benefit of our children and ourselves, and for discussing ‘health’ and ‘improvement’ in ethical and not only in technical terms. The protection and promotion of healthy people, sustainable societies, and diverse and stable political bodies depend on basic economic accomplishments, healthy food, harmonious communities, preservation and diversity of cultures and environments, on individual dignity and social recognition, i.e. on gross happiness products [GHP’s] and not only on gross national products [GNP’s] measured in economic terms only.